find the zeros of...

Nov 2009
717
133
Wahiawa, Hawaii
since this is already factored out

f(x)=x^2(x+3)(x^2-1)?


show work please
presume you mean find the values of x so that

\(\displaystyle x^2(x+3)(x^2-1) = 0\)

since this is already factored out. then setting any one of the factors to zero will work so..

if \(\displaystyle x^2 = 0\) then \(\displaystyle x = 0\)
if \(\displaystyle x+3=0\) then \(\displaystyle x=-3\)
if \(\displaystyle x^2-1 = 0\) then\(\displaystyle x= 1 \)or \(\displaystyle x= -1\)